A secondary analysis to inform a clinical decision rule for predicting skull fracture and intracranial injury in children under age 2. Issue 1 (5th November 2019) - Stone, Elizabeth L.; Davis, Leslie L.; McCoy, Thomas P.; Travers, Debbie; Van Horn, Elizabeth; Krowchuk, Heidi V.
Abstract: The purpose of this study was to identify factors associated with the risk of closed head injury (CHI) in children under age 2 years with suspected minor head injuries based on age‐appropriate, or near age‐appropriate, mental status on an exam. The study was a secondary data analysis of a public‐use dataset from the largest prospective, multicenter pediatric head injury study found in the current literature. An existing, validated clinical decision rule was examined using a sample of 3, 329 children under age 2 to determine whether it, or the individual variables within it, could be utilized alone, or in conjunction with other variables to accurately predict the risk of underlying CHI in this sample. Results indicated that the keys to an accurate triage assessment for children under age 2 with suspected minor head injuries include the ability to identify the specific skull region injured, the ability to assess for the presence and size of any scalp hematoma, the ability to identify signs of altered mental status in this age group, and having access to accurate information regarding the child's age and the details of the injury mechanism. The findings from this study add to the body of knowledge regarding what factors are associated with CHI in children under age 2 with suspected minor head injuries and could be used to inform age‐specific recommendations for children under age 2 in triage, educational resources, and national trauma criteria.